Linguistic Interference between Arabic and Indonesian in Daily Conversations: A Field Study on the Female Students of Ma'had Aisyah, Bogor - Motea Naji Dabwan Hezam; Dadan Mardani; Mahmud Mahmud; Rohanda Rohanda (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This study investigates the phenomenon of linguistic interference between Arabic and Indonesian in the daily conversations of students at Ma’had Aisyah binti Abi Bakr, Bogor. Using a qualitative field approach, data were collected through observation, interviews, and documentation of real-life dialogue. The findings reveal four types of interference: lexical, syntactic, phonological, and pragmatic. Lexical interference includes Indonesian vocabulary inserted into Arabic sentences; syntactic interference involves sentence patterns influenced by Indonesian structure; phonological interference appears in the mispronunciation of Arabic phonemes; and pragmatic interference includes the use of Indonesian discourse particles such as dong, loh, and nih in Arabic utterances. The causes of these interferences include the dominance of the mother tongue, limited mastery of Arabic, and social-affective factors. These interferences are not merely errors but reflect communication strategies in a bilingual learning context. The study recommends pedagogical responses that integrate communicative and language-awareness-based Arabic teaching to minimize negative interference and promote more effective language acquisition.